Analysis of Ability to Write and Read Letters in Children With Special Needs at SDN 1 Picungremuk - Anggia Suci Pratiwi; Sunanih; Lusi Andriyani Lusi (LPPM Universitas Buana Perjungan Karawang, 2021)
Based on the results of observations in class V SDN 1 Picungremuk, it shows that in the learning process the teacher has not used the right learning method so that learning is less interesting and students think writing and reading is a difficult subject. The purpose of this study was to determine the development of writing and reading for children with special needs, to determine the development of children with special needs after being given picture cards during the study. The method used in this research is qualitative research with the Grounded theory approach, which is to produce a general explanation of a process, researchers focus on different processes or actions from time to time, develop theories of these processes or actions, take notes to be collected and analyzed, carry out interviews, and data analysis. The findings showed that the use of media in recognizing the letters A-Z in children with special needs can run well through various stages and approaches, creating a fun and interesting learning atmosphere. Even though the child still has difficulty remembering the letters, there has been progress in writing because the child has a habit of writing these letters.